2010
DOI: 10.1523/jneurosci.3445-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Multisegmental Aδ- and C-Fiber Input to Neurons in Lamina I and the Lateral Spinal Nucleus

Abstract: Spinal lamina I and the lateral spinal nucleus (LSN) receive and integrate nociceptive primary afferent inputs to project through diverse ascending pathways. The pattern of the afferent supply of individual lamina I and LSN neurons through different segmental dorsal roots is poorly understood. Therefore, we recorded responses of lamina I and LSN neurons in spinal segments L4 and L3 to stimulation of six ipsilateral dorsal roots (L1-L6). The neurons were viewed through the overlying white matter in the isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 44 publications
7
51
1
Order By: Relevance
“…They had small somata and relatively un-branched dendritic trees. These DLF neurons were located only in the dorsal laminae of the gray matter and in the dorsolateral white matter (the latter is consistent with the lateral spinal nucleus of rodents Waldron, 1968, 1969;Jiang et al, 1999;Olave and Maxwell, 2004;Dutton et al, 2006;Pinto et al, 2010). Few neurons were found in lamina VII.…”
Section: Dlf Projectionssupporting
confidence: 72%
“…They had small somata and relatively un-branched dendritic trees. These DLF neurons were located only in the dorsal laminae of the gray matter and in the dorsolateral white matter (the latter is consistent with the lateral spinal nucleus of rodents Waldron, 1968, 1969;Jiang et al, 1999;Olave and Maxwell, 2004;Dutton et al, 2006;Pinto et al, 2010). Few neurons were found in lamina VII.…”
Section: Dlf Projectionssupporting
confidence: 72%
“…Previous work indicates that most neurons located in lamina I of the spinal cord, being either excitatory or inhibitory, receive monosynaptic input from either A␦-fibers and/or C-fibers (Yoshimura and Jessell, 1990;Dahlhaus et al, 2005;Yasaka et al, 2007;Pinto et al, 2010), and many also express group I mGluRs (Alvarez et al, 2000). In the present study, we recorded from unidentified lamina I neurons and showed that LTP GABA could Figure 7.…”
Section: Potential Functional Consequences Of Ltp Gaba In Nociceptivesupporting
confidence: 48%
“…Nevertheless, this is still higher than the success rate of recovering biocytin filled cells in our previous work on LSN neurons (30%, Pinto et al, 2010). Probably due to the same reason, we could not achieve presynaptic labelling to an extent that would have allowed identification of synaptic connections in the initial trials, thus, later we excluded biocytin from the cell-attached pipette to reduce contamination of the preparation that would have made it difficult to trace the axon trajectories.…”
Section: Technical Considerationsmentioning
confidence: 80%
“…In terms of functionality, these ultra-short propriospinal connections are of questionable importance, but may increase the complexity of intraspinal divergence and convergence (Pinto et al, 2010) of primary afferent inputs. Synaptic delay in the recorded monosynaptic connections showed a large variation, but even the longest observed latencies would be compatible with putative long axodendritic pathways and recording conditions at room temperature .…”
Section: Short Intersegmental Connections Of Lamina I and The Lsn Arementioning
confidence: 99%